Role of medicines of unknown identity in adverse drug reaction-related hospitalizations in developing countries: Evidence from a cross-sectional study in a teaching hospital in the Lao People's Democratic Republic. - Caillet, C; Sichanh, C; Assemat, G; Malet-Martino, M; Sommet, A; Bagheri, H; Sengxeu, N; Mongkhonmath, N; Mayxay, M; Syhakhang, L; Lapeyre-Mestre, M; Newton, P; et al. (Springer, 2017)
Introduction The health dangers of medicines of unknown identity (MUIs) [loose pharmaceutical units repackaged in individual bags without labelling of their identity] have been suspected in L/MICs. Using visual and analytical tools to identify MUIs, we investigated the frequency of, and factors associated with, adverse drug reaction (ADR)- related hospitalizations in a central hospital in Vientiane Capital, Lao People’s Democratic Republic (PDR). Methods All unplanned admissions, except for acute trauma and intentional overdose, were prospectively recorded during a 7-week period in 2013, leading to include 453 adults hospitalized for C24 h. The patients or their relatives were interviewed to complete the study questionnaire. MUIs suspected of being involved in ADR(s) were identified through comparison of visual characteristics of tablets/capsules with that of reference medicines (photograph tool), and by proton nuclear magnetic resonance and mass spectrometry analyses. Factors associated with ADRs were identified by multivariate logistic regression. Results The frequency of hospitalizations related to an ADR was 5.1% (23/453, 95% confidence interval [CI] 3.1–7.1). Forty-eight (12.8%) patients used MUI(s) in the last 2 weeks preceding hospitalization. They were more likely to be hospitalized because of an ADR (adjusted odds ratio 4.5, 95% CI 1.7–11.5) than patients using medicines of known identity. MUIs were mainly involved in bleeding gastroduodenal ulcers. The photograph tool led to the misidentifications because of look-alike pharmaceutical units in the medicines photograph collection. Conclusion According to the results of this study, there is a need to ensure appropriate labelling of medicines at dispensing and to provide well-suited tools to identify MUIs in clinical settings to improve drug safety and patients’ carein developing countries with limited capacities for drug analysis.